Pengembangan Konten Transmedia Program Innovation Day PT Telekomunikasi Indonesia Tbk. - Mella Rahensa; Agus Pratondo; Rikman Roedavan (Universitas Telkom, 2024)
Limitations of face-to-face activities during the COVID-19 pandemic have led many companies to shift their events online,broadcasting them on specific platforms such as YouTube and Instagram to ensure that operations continue effectivelydespite the restrictions. In this regard, PT Telekomunikasi Indonesia Tbk. has provided a platform for sharing knowledgethrough the online program called Innovation Day, which is live-streamed on the Microsite Innovation Day and also onYouTube. Since the event is conducted online, it requires a set of asets such as animations, videos, designs, and onlinemedia collectively referred to as the multimedia set called ’Transmedia.’ The ultimate goal is to create interactive videoproductions that will be showcased on the website and YouTube channel of Innovation Day, providing valuable knowledgeto both the internal Telkom Grup audiens and the general publik through the development of transmedia content for theInnovation Day program. The total production of Innovation Day content has reached 23 videos, consisting of 19 publicbroadcasts and 4 internal Telkom Group broadcasts